Reduction Mammoplasty: Desire or Necessity (Bangladesh Journal of Plastic Surgery, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bdjps.v3i2.18241 Bangladesh Journal of Plastic Surgery July 2012, 3(2): 29-31